OUTSOURCING PENDIDIKAN: ANALISIS KRITIS TREN SEKOLAH DAN MADRASAH MENGGANDENG LEMBAGA BIMBINGAN BELAJAR (OUTSOURCING EDUCATION: A CRITICAL ANALYSIS OF THE TREND OF SCHOOLS AND MADRASAHS PARTNERING WITH PRIVATE TUTORING INSTITUTIONS) - Mohammad Muslih; Nuraini, Nuraini (Universitas Muhammadiyah Ponorogo, 2025)
The phenomenon of schools and madrasahs sending students to language courses or inviting private tutoring reflects a transformation of formal education increasingly reliant on external institutions. This practice emerges in response to competitive pressures, parental demands, and the need to enhance academic achievement. While seemingly rational, it also reveals hidden dimensions related to efficiency, the commodification of education, and the shifting of teaching responsibilities. This article analyzes the phenomenon by integrating the theories of shadow education, outsourcing, and commodification, and compares practices in Indonesia with countries such as South Korea, Japan, and Egypt. The analysis reveals a paradox: private tutoring can improve student academic outcomes while simultaneously weakening teacher roles and formal school functions, generating ethical and social issues such as conflicts of interest and educational inequality. The study emphasizes the importance of regulation, transparency, and a balanced integration between formal and supplementary education. Through a holistic approach, private tutoring can complement rather than replace formal education, fostering an effective, inclusive, and sustainable education system